Expression of Trypanosoma congolense antigens in spodoptera frugiperdia insect cells - Urakawa, T.; Eshita, Y.; Fukuma, T.; Hirumi, H.; Hirumi, K.; Majiwa, Phelix A.O. (Elsevier, 1995)
Transcripts which encode two metacyclic-form-specific variable surface glycoproteins (mVSGs) of Trypanosoma congolense IL3000 have been cloned into baculovirus expression vectors using a novel transfer vector, pAcL11. One of the recombinant baculoviruses (AcVSG1) expressed a mVSG as a glycoprotein with a signal peptide which was cleaved in this expression system, whereas the other one (AcVSG2) expressed an uprocessed protein. From 1 liter of culture containing 109 spodoptera frugiperda cells infected with the recombinant baculoviruses, 10 and 30 mg of mVSG1 and mVSG2, respectively, were obtained. Monospecific polyclonal antibodies produced by immunization of mice with the recombinant proteins reacted specifically with the respective proteins and showed no cross-reactivities between mVSG1 and mVSG2 in imunoblot assays. The antibodies to each of the proteins stained only the surface of a proportion of intact fixed T. congolense IL3000 metacyclic forms. It was possible to determine from these studies that, on the average, the parasites expressing mVSG1 constitute approximately 45 percent of the metacyclic population of T. congolense IL3000 maintained in in vitro cultures, whereas those that express mVSG2 constitute approximately 20 percent.